Comparative Studies on Bioactive Constituents in Hawk Tea Infusions with Different Maturity Degree and Their Antioxidant Activities. (15th July 2014) - Yuan, Ming; Jia, Xuejing; Ding, Chunbang; Yuan, Shu; Zhang, Zhongwei; Chen, Yanger
Abstract : Hawk tea ( Litsea coreana var. lanuginose ) is a very popular herbal tea in the southwest of China. According to the maturity degree of raw materials, Hawk tea can usually be divided into three types: Hawk bud tea (HB), Hawk primary leaf tea (HP), and Hawk mature leaf tea (HM). In this study, some of the bioactive constituents and antioxidant properties of the three kinds of Hawk tea infusions were comparatively investigated. The results showed that the contents of total flavonoids, vitamin C, and carbohydrates in Hawk bud tea infusion (HBI) were higher than those in Hawk primary leaf tea infusion (HPI) and Hawk mature leaf tea infusion (HMI). HPI had higher contents of total polyphenols and exhibited better DPPH radical scavenging activity and ferric reducing activity power. HBI could provide more effective protection against erythrocyte hemolysis. As age is going from bud to mature leaf, the ability to inhibit the formation of low density lipoprotein (LDL) conjugated diene and the loss of tryptophan fluorescence decreased. The bioactive constituents and antioxidant activities of Hawk tea infusions were significantly affected by the maturity degree of the raw material.